Discrete multivariate analysis :Theory and practice /[by] Yvonne M. M. Bishop, Stephen E. Fienberg and Paul W. Holland. With the collaboration of Richard J. Light and Frederick Mosteller. - Bishop, Yvonne M. M.(Yvonne Millicent Mahala)
Bibliography: p. [531]-542.